2003
DOI: 10.3354/meps263113
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects along a UV-B gradient on species composition and diversity of a shallow-water macrobenthic community in the western Baltic

Abstract: Although the 'intermediate disturbance hypothesis' (IDH) was originally postulated for marine hard-bottom communities, it has rarely been tested for this community type. We experimentally examined the effects of ambient plus artificially enhanced UV-B radiation (eUV-BR) along an intensity gradient on the abundance of individual species, species composition, and diversity of a macrobenthic community in the western Baltic, Germany. Plots were either exposed each day for 0.5, 1, 2, 4, and 8 h to the maximum expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 75 publications
4
17
0
Order By: Relevance
“…This study has revealed that unimodal diversitydisturbance relationships can result from different processes, corroborating studies of macrobenthic com- (Molis et al 2003). Both the variation in processes generating unimodal diversity patterns as well as the variety in diversity-disturbance relationships themselves (Mackey & Currie 2001) indicate that disturbance alone may not predict community diversity sufficiently well.…”
Section: Discussionsupporting
confidence: 54%
“…This study has revealed that unimodal diversitydisturbance relationships can result from different processes, corroborating studies of macrobenthic com- (Molis et al 2003). Both the variation in processes generating unimodal diversity patterns as well as the variety in diversity-disturbance relationships themselves (Mackey & Currie 2001) indicate that disturbance alone may not predict community diversity sufficiently well.…”
Section: Discussionsupporting
confidence: 54%
“…Finally, several seaweed species, e.g. green filamentous forms, seem particularly well adapted to recruit at UVexposed sites in the upper eulittoral, i.e., where UV-irradiance is strongest on the shore, and it was experimentally demonstrated that their abundance correlates positively with UV-exposure time (Molis et al 2003). The invasion of sites high on the intertidal shore might be a selective advantage, as this guarantees a relative shorter exposure to grazers compared to sites lower on the shore.…”
Section: Successionmentioning
confidence: 99%
“…Only a few studies assessed UV-effects during species succession of shallow-water seaweed-dominated communities (Santas et al 1998;Molis et al 2003;Molis and Wahl 2004;Wahl et al 2004;Dobretsov et al 2005). Surprisingly in all but one study (Dobretsov et al 2005), UV-effects were only apparent during the early phase of succession.…”
Section: Successionmentioning
confidence: 99%
“…Baker 1995, Bingham & Reitzel 2000, Chiang et al 2003. Only a few studies have examined the effect of UVR on benthic communities (Santas et al 1998a,b, Lotze et al 2002, Molis et al 2003, Molis & Wahl 2004. For example, Santas et al (1998b) investigated the effect of UV-A and UV-B radiation on benthic diatoms in a coral reef in the Caribbean.…”
Section: Introductionmentioning
confidence: 99%